2020
DOI: 10.3934/krm.2020004
|View full text |Cite
|
Sign up to set email alerts
|

Hypocoercivity of linear kinetic equations via Harris's Theorem

Abstract: We study convergence to equilibrium of the linear relaxation Boltzmann (also known as linear BGK) and the linear Boltzmann equations either on the toruswith a confining potential. We present explicit convergence results in total variation or weighted total variation norms (alternatively L 1 or weighted L 1 norms). The convergence rates are exponential when the equations are posed on the torus, or with a confining potential growing at least quadratically at infinity. Moreover, we give algebraic convergence rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The linear Boltzmann equation was first shown to converge to equilibrium by Hérau in [31] and also falls under the scope of the powerful general theorem in [22]. In [16], written by the authors and others, we show that Harris's theorem from Markov process theory provides an alternative way of showing convergence to equilibrium for the linear Boltzmann equation amongst other equations. The run and tumble equation differs from the linear Boltzmann, and similar hypocoercive equations, in two key ways.…”
Section: Motivation Methodology and Noveltymentioning
confidence: 77%
See 1 more Smart Citation
“…The linear Boltzmann equation was first shown to converge to equilibrium by Hérau in [31] and also falls under the scope of the powerful general theorem in [22]. In [16], written by the authors and others, we show that Harris's theorem from Markov process theory provides an alternative way of showing convergence to equilibrium for the linear Boltzmann equation amongst other equations. The run and tumble equation differs from the linear Boltzmann, and similar hypocoercive equations, in two key ways.…”
Section: Motivation Methodology and Noveltymentioning
confidence: 77%
“…This fact was exploited by the first author in [26] where we used Harris's theorem to find existence of a steady state for a non-linear kinetic equation with nonequilibrium steady states. Moreover, in [16], we showed that Harris's theorem can be applied efficiently to kinetic equations with nonlocal collision operators to obtain quantitative hypocoercivity results. In conclusion, the classical tools from hypocoercivity are difficult to apply on the run and tumble equation but Harris's approach gives promising results.…”
Section: Motivation Methodology and Noveltymentioning
confidence: 99%
“…This is true for many distributions which decay only polynomially at infinity. For the linear relaxation Boltzmann equation convergence to equilibrium results in a polynomially weighted L 1 space exist in the paper [12] due to the author and collaborators. This polynomially weighted L 1 space allows for an even wider class of initial data than is considered in this paper.…”
Section: Previous Workmentioning
confidence: 99%
“…This polynomially weighted L 1 space allows for an even wider class of initial data than is considered in this paper. The work [12] uses Harris's theorem from Markov process theory rather than the entropy method used here which results in a less explicit rate of decay. • If we want to eventually study non-linear equations then it is often the case that strong spaces like f ∈ L 2 (µ −1 )/h ∈ L 2 (µ) will not be a natural space for the equation.…”
Section: Previous Workmentioning
confidence: 99%
“…Concerning Fokker-Planck equations and kinetic Fokker-Planck equations we shall quote [73,59] and [23], as well as the references therein. We also mention the results concerning degenerate linear transport equations [31,12,20], as well as degenerate linear Boltzmann equations [53]. Finally, the free transport equation with diffusive or Maxwell boundary condition has been tackled in [3,62,13] for instance.…”
Section: Weakly Coercive Operatorsmentioning
confidence: 99%